The Impact of the Trafficking Victims Protection Act of 2000 on Trends in Federal Sex Trafficking Cases - Judge, Shana M. (Criminal justice policy review, 2018)
In this study, we addressed the need for empirical research on human trafficking by compiling unique data relating to criminal charges filed in federal judicial districts and using these data to examine trends in sex trafficking-related cases, as well as the impact on those trends of the Trafficking Victims Protection Act of 2000 (TVPA). Results from our regression models indicate that the proportion of all charges filed by federal prosecutors that involved sex trafficking and related cases increased significantly between 1994 and 2007. The rate of increase, however, slowed in the time period following the passage of the TVPA, suggesting that the TVPA may have helped to mitigate increases in new cases. In addition, our results show statistically significant inverse relationships between immigration and sex trafficking-related charges filed, providing new evidence to support the possibility that some sex trafficking-related cases may be being prosecuted as immigration cases instead.